Industrial experiences from evolving measurement systems into self‐healing systems for improved availability. (16th August 2017) - Staron, Miroslaw; Meding, Wilhelm; Tichy, Matthias; Bjurhede, Jonas; Giese, Holger; Söder, Ola
Summary: Automated measurement programs are an efficient way of collecting, processing, and visualizing measures in large software development companies. The number of measurements in these programs is usually large, which is caused by a diversity of the needs of the stakeholders. In this paper, we present the application of the self‐healing concepts to assure the availability of measurements to the stakeholders without the need for effort‐intensive and costly manual interventions of the operators. We study the measurement infrastructure at one of the development units of a large infrastructure provider. In this paper, we present how the Monitor, Analyze, Plane, and Execute with Knowledge model was instantiated in a simplistic manner to reduce the need for manual intervention in the operation of the measurement systems. Based on the experiences from the 2 cases studied in this paper, we show how an evolution toward self‐healing measurement systems is done both with a dedicated failure taxonomy and with an effective straightforward handling of the most common errors in the execution. The mechanisms studied and presented in this paper show that self‐healing provides significant improvements to the operation of the measurement program and reduces the need for daily oversight by an operator for the measurement systems.